Effects of swimming exercise and RLN2 induction on relaxin levels, MMP-13, TGFβ expression in the pubic cartilage of pregnant rats - Ika Oktaviani; Titin Andri Wihastuti; Bambang Rahardjo; Endang Sri Wahyuni; Bilqisthi Ari Putra (GarVal Editorial Ltda., 2022)
Context: Swimming exercises can be used as an intervention to maintain the stability of the synthesis of the pubic symphysis cartilage. Aims: To evaluate the effects of swimming exercise on relaxin levels, MMP-13, TGFβ expression in pubic cartilage at pregnant rats with induction of RLN2 gene. Methods: Thirty-six female Wistar rats (six in each group) were impregnated with 24 male rats (1:1). Three groups had swimming exercises for 60 min per day, and the other groups were treated as the control group. Two groups were given subcutaneous RLN2 gene. Relaxin plasma was collected from the sinus retro-orbital and performed twice on the eighth day and the 20th of pregnancy. The pubic symphysis of the rats was collected on the 20th day of pregnancy, and the decalcification process was carried out before making histological preparations. Results: There was an increase in the amount of relaxin in the relaxin-induced group after 24 h induction (p=0.000). Relaxin levels of pregnant rats on the 20th day correlated with the expression of MMP-13, p=0.029; R2=0.447. In the treatment group, relaxin levels and MMP-13 expression were lower than the non-treatment group, p=0.005 and p=0.000, respectively. In contrast, there was a higher expression of TGFβ in the treatment group, p=0.000. Conclusions: Relaxin plasma levels have a significant correlation with the expression of MMP-13, and swimming exercise increases the expression of TGFβ and decreases relaxin levels and MMP-13 expression in the pubic cartilage.